2004
DOI: 10.1007/s10024-004-2020-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Vascular Obstructive Lesions: Nosology and Reproducibility of Placental Reaction Patterns

Abstract: The purpose of this study was to assemble and test the reliability of a complete set of the placental reaction patterns seen with chronic fetal vascular obstruction in the hope that this might provide a standardized diagnostic framework useful for practicing pathologists. Study cases (14 with fetal vascular obstructive lesions, 6 controls) were reviewed blindly by seven pathologists after agreement on a standard set of diagnostic criteria. Majority vote served as the gold standard and 80% of the 180 diagnoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(177 citation statements)
references
References 33 publications
9
163
0
5
Order By: Relevance
“…In addition, previous studies have showed that interrater reliability for diagnosing histologic evidence of vasculature-related pathology is not high (22,24,31), perhaps because there is a lack of agreement as to what constitutes a critical mass of findings for the designation ''positive.'' Major strengths of this study include the sample, which was recruited from multiple community clinics and was shown to be highly comparable to community women giving birth during this period.…”
Section: !1 þmentioning
confidence: 99%
“…In addition, previous studies have showed that interrater reliability for diagnosing histologic evidence of vasculature-related pathology is not high (22,24,31), perhaps because there is a lack of agreement as to what constitutes a critical mass of findings for the designation ''positive.'' Major strengths of this study include the sample, which was recruited from multiple community clinics and was shown to be highly comparable to community women giving birth during this period.…”
Section: !1 þmentioning
confidence: 99%
“…Avascular villi were defined by Ն15 affected terminal villi per section. 13 Chorangiosis was defined by 10 villi with Ն10 vascular channels. 14 Tenney-Parker change (excessive syncytial knotting) was defined by Ն30% of the tertiary villi with syncytial buds.…”
Section: Classification Of Placental Findingsmentioning
confidence: 99%
“…10 In the present study incidence of chronic villitis was 14% in AGA group and 32% in IUGR group. In the present study, the placentas were significantly smaller in IUGR group than AGA group.…”
Section: Iud Stillborn Low Apgar Perinatal Deathmentioning
confidence: 78%